Emergence of ceftazidime/avibactam resistance in carbapenem-resistant Klebsiella pneumoniae in China. (January 2020) - Zhang, P.; Shi, Q.; Hu, H.; Hong, B.; Wu, X.; Du, X.; Akova, M.; Yu, Y.
Abstract: Objectives: The aim was to investigate the activity of ceftazidime/avibactam (CAZ/AVI) against carbapenem-resistant Klebsiella pneumoniae (CRKP) and identify the resistance mechanisms before CAZ/AVI coming to Chinese market. Methods: Clinical CRKP isolates were continuously collected from 36 tertiary hospitals in China from 1 March 2017 to 31 July 2017. CAZ/AVI MICs were determined by agar dilution method. CAZ/AVI resistant isolates were submitted to whole genome sequencing. The copy number and relative expression of bla KPC were determined by quantitative PCR. Results: A total of 872 CRKP isolates were collected, and MIC50 and MIC90 of CAZ/AVI were 4 and 8 mg/L. The resistant rate of CAZ/AVI was 3.7% (32/872). Among the resistant isolates, 53.1% (17/32) were metallo-β-lactamase-producing K. pneumoniae (MBL-KP), 40.6% (13/32) were Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-KP) and 6.3% (2/32) produced both MBL and KPC. One of the KPC-KP with high level CAZ/AVI resistance (>128 mg/L) harboured mutated bla KPC-2 (D179Y). In 12 wild-type bla KPC-2 isolates, the relative copy number and expression of bla KPC-2 gene were 2.5-fold and 2.7-fold higher than that in the CAZ/AVI MIC ≤0.5 mg/L group (p < 0.05), and when added avibactam at a fixed concentration of 8 mg/L, 91.7% (11/12) isolates could restore susceptibility. Conclusions: Resistance against CAZ/AVI in CRKP emerged before clinical use of CAZ/AVI in China, although most of the CRKP isolates maintained the susceptibility. MBL production, bla KPC-2 point mutation and high KPC expression played an important role in CAZ/AVI resistance.